Withdrawal after buprenorphine induction: The fentanyl effect. Issue 46 (3rd December 2021) - Knopf, Alison
Abstract : Opioid‐dependent patients who are administered buprenorphine have reported anecdotally that the medication causes withdrawal symptoms. A recent study ("Evidence of Buprenorphine‐precipitated Withdrawal in Persons Who Use Fentanyl, " by Neil B. Varshneya, Ph.D., and colleagues, published in the Nov. 23 issue of the Journal of Addiction Medicine ) based on patient interviews found that patients who were administered buprenorphine within 24 hours of illicit fentanyl use were more likely to have severe withdrawal symptoms than patients administered methadone, or than patients who waited 24 hours.